Disciplinary trial guarantees for a university faculty member in Libyan law (مجلة أبحاث قانونية, 2023)
The administration has discretionary authority to consider any action taken by a faculty member that violates the requirements of the job as a disciplinary violation requiring disciplinary punishment. In return, to prevent the administration from misusing its authority, the legislator restricted it in accordance with Law No. 12 of 2010 issuing the Labor Relations Law, and the decision of the People’s Committee. Formerly General No. 501 of 2010 AD regarding issuing a regulation regulating higher education, and the administrative judiciary with a set of guarantees that must be taken into account during the disciplinary trial, as the penalty of invalidation of its decisions was stipulated in the event that the administration violates this, and this is what this research will discuss.